Pengaruh Pembelajaran Berbasis Proyek Terarium Ulat Terhadap Pemahaman Dan Keterampilan Proses Sains Siswa Kelas III SD - Rakhmania, Vinda Heda; Ibrohim, Ibrohim; Suharti, Suharti (Jurnal Ragam Pengabdian, 2026)
2022 PISA data shows that the scientific literacy skills of Indonesian students are still below average. These conditions indicate that students' ability to understand science concepts, apply scientific knowledge, and use science process skills in solving problems still needs to be improved. Based on observations and interviews in primary schools, it was found that there is still a lack of use of learning models and approaches, and teachers do not provide alternative learning access options for students. So this research aims to examine the influence of project-based learning on students' science understanding abilities and process skills. The research design used in this research is a quasi-experimental design. The research subjects consisted of 30 elementary school students consisting of 2 classes, namely 15 experimental class students and 15 control class students. The experimental class received project-based learning treatment while the control class received a scientific approach learning treatment. Data on students' science understanding abilities and process skills are obtained from the test instrument on students' science understanding abilities and process skills. Data analysis was carried out using the Independent Sample t Test at the significance level (sig < 0.05). The research results show that there are differences in students' science understanding abilities and process skills in the classroom with project-based learning and the classroom with a scientific approach. This can be seen from the increase in Posttest scores obtained in project-based learning classes compared to scientific approach classes. The independent sample t test showed a probability significance value of 0.000, which is smaller than α 0.05 (sig < 0.05). Therefore, PjBL has proven effective for improving science understanding abilities and science process skills of elementary school students.